The promotional discourse of liberation movements in Zimbabwe: a textual analysis of political jingles - Manyawu, Andrew T. (Taylor & Francis (Routledge), 2016)
Zimbabwe's ruling Zimbabwe African National Union (Patriotic Front) (ZANU-PF) has developed promotional discourse that is packaged in various forms and spread through such institutions as the media. This article is concerned with the discursive aspect of songs used as ZANU-PF promotional jingles on national radio and television to persuade the audience to buy into the party's thinking. Purposively sampled jingles are subjected to close textual examination from a perspective of folklorisation approached from within the framework of critical discourse analysis (CDA). The article argues that lyrics of jingles by the ZANU-PF group Mbare Chimurenga Choir (MCC) use folklorisation discourse strategies to appropriate the national heritage to ZANU-PF while alienating rival parties from that heritage. The strategies that the MCC uses to enhance folklorisation thus exploit a presumed desire to be associated with the national heritage along with the presumed fear of alienation and ridicule to establish ZANU-PF hegemony in Zimbabwe